2019
DOI: 10.1177/0333102418821669
|View full text |Cite
|
Sign up to set email alerts
|

Greater occipital nerve block in migraine prophylaxis: Narrative review

Abstract: Objectives The importance and popularity of peripheral nerve block procedures have increased in the treatment of migraine. Greater occipital nerve (GON) block is a commonly used peripheral nerve block method, and there are numerous researches on its use in migraine treatment. Materials and methods A search of PubMed for English-language randomized controlled trials (RCT) and open studies on greater occipital nerve block between 1995 and 2018 was performed using greater occipital nerve, headache, and migraine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 33 publications
3
55
0
4
Order By: Relevance
“…A recent review by Inan et al in 2019 evaluated the role of GON block in migraine prophylaxis but did not focus on CM only. 30 They reviewed 14 trials, 7 of which were randomized controlled trials (RCTs). Of these, 5 had placebo-controlled arms and 2 studied the effects of addition of steroids to GON block.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review by Inan et al in 2019 evaluated the role of GON block in migraine prophylaxis but did not focus on CM only. 30 They reviewed 14 trials, 7 of which were randomized controlled trials (RCTs). Of these, 5 had placebo-controlled arms and 2 studied the effects of addition of steroids to GON block.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, large occipital nerve blockade was performed for chronic migraine, tension-type headache and cervicogenic headache, and a significant reduction in pain intensity was observed in patients with chronic migraine. (12).…”
Section: Current Medical Research and Opinionmentioning
confidence: 99%
“…This connection of the trigeminal and occipital/ cervical system is the mechanistic justification for blocking the greater occipital nerve (GON-block) as a treatment option for headache patients. This has long been utilised in clinical practice for primary headaches such as cluster headache (12), but there is conflicting evidence for its efficacy in migraine (13). Open trials have reported some reduction in frequency and intensity of attacks (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%